If Fascism Is Not Really On the March, Then Why the Constant ‘Brown Scares’? - Bar-On, Tamir (Revista de Estudios Globales. Análisis Histórico y Cambio Social, 2023)
Today “Brown Scares” are the order of the day in many countries in Europe and the Americas. Why is this the case in anti-fascist age when fascism is not really on the march? I want to advance the argument that there are few fascists remaining today in Euro-American societies, but that “Brown Scares” have been revived in various decades since the 1950s. These “Brown Scares” are used by the establishment to undermine political opponents and to engage in more authoritarian mechanisms against enemies of the current pro-liberal and pro-capitalist establishment.